Design conception of a food dehydrator - Kapitány, Pálma; Rónai, László (Design of Machines and Structures, 2024)
Nowadays, the household is unimaginable without the three main pillars of the technical field, which are mechanical engineering, electrical engineering and IT. The paper deals with the design conception of a food dehydrator unit. These types of devices are capable of drying fruits and mushrooms. The article covers the design conception of a specific version, and then by building a test system, it becomes possible to check the correctness of the control program code belonging to the system.